I DRONI PER L’AGRICOLTURA - Lemon, Salt (GEOmedia, 2014)
New trends in precision farming show the deployment of different types of technology among which Infrared photography is becoming progressively relevant. Thanks to the special op tical behavior shown by plants in the band of infrared radiation, it is po ssible to measure indexes from infrared photos -such as NDVI (Normalized Difference Vegetation Index)-able to assess the health status of a crop . These photos, depicting vegetation in brilliant red, yellow and other colors can detect problems such as lack of nutrients, infection of parasites or water stress. Following this technology evolution, different types of cameras have becom e available with a low weight and an affordable cost to be used on small, unmanned aerial vehicles. Salt & Lemon is carrying out various experimental activities along with academic bod ies, research centers and agronom ists in order to exploit drones features in agriculture refining the techniques for capturing and analyzing data to provide farmers with the most useful health assessment of their crop s.